Augmented Lipocalin-2 Is Associated with Chronic Obstructive Pulmonary Disease and Counteracts Lung Adenocarcinoma Development - Treekitkarnmongkol, Warapen; Hassane, Maya; Sinjab, Ansam; Chang, Kyle; Hara, Kieko; Rahal, Zahraa; Zhang, Jiexin; Lu, Wei; Sivakumar, Smruthy; McDowell, Tina L; Kantrowitz, Jacob; Zhou, Jianling; et al. (American journal of respiratory and critical care medicine, 2021)
Early pathogenesis of lung adenocarcinoma (LUAD) remains largely unknown. We found that, relative to wild-type littermates, the innate immunomodulator (lipocalin-2) was increased in normal airways from mice with knockout of the airway lineage gene ( ) and that are prone to developing inflammation and LUAD. Yet, the role of LCN2 in lung inflammation and LUAD is poorly understood. Delineate the role of induction in LUAD pathogenesis. Normal airway brushings, uninvolved lung tissues, and tumors from mice before and after tobacco carcinogen exposure were analyzed by RNA sequencing. mRNA was analyzed in public and in-house data sets of LUAD, lung squamous cancer (LUSC), chronic obstructive pulmonary disease (COPD), and LUAD/LUSC with COPD. LCN2 protein was immunohistochemically analyzed in a tissue microarray of 510 tumors. Temporal lung tumor development, gene expression programs, and host immune responses were compared between and / littermates. was progressively elevated during LUAD development and positively correlated with proinflammatory cytokines and inflammation gene sets. was distinctively elevated in human LUADs, but not in LUSCs, relative to normal lungs and was associated with COPD among smokers and patients with LUAD. Relative to mice, / littermates exhibited significantly increased lung tumor development concomitant with reduced T-cell abundance (CD4 ) and richness, attenuated antitumor immune gene programs, and increased immune cell expression of protumor inflammatory cytokines. Augmented LCN2 expression is a molecular feature of COPD-associated LUAD and counteracts LUAD development by maintaining antitumor immunity.